Invisibility, Superficiality and Plasticity: Three Hypotheses on Smart Cameras - Vidal Junior, Icaro Ferraz (2015)
This paper proposes three hypotheses concerning the smart cameras: 1) there is a tendency of the algorithmically inscribed diagrams on the surface of the image in order to make themselves invisible; 2) the emphasis on superficiality of conducts is linked to the replacement of the privileged locus of subjectivity towards the surface of the bodies in the second half of the twentieth century and to a contemporary emphasis on action; 3) the predictive and anticipatory nature of intelligent devices of visibility is an important indicator of a contemporary crisis here formulated as a crisis of plasticity and habit.